Muconic acid production from glucose and xylose in Pseudomonas putida via evolution and metabolic engineering - Ling, Chen; Peabody, George L.; Salvachúa, Davinia; Kim, Young-Mo; Kneucker, Colin M.; Calvey, Christopher H.; Monninger, Michela A.; Munoz, Nathalie Munoz; Poirier, Brenton C.; Ramirez, Kelsey J.; St. John, Peter C.; Woodworth, Sean P.; et al. (Nature communications, 2022)
Muconic acid is a bioprivileged molecule that can be converted into direct replacement chemicals for incumbent petrochemicals and performance-advantaged bioproducts. In this study, Pseudomonas putida KT2440 is engineered to convert glucose and xylose, the primary carbohydrates in lignocellulosic hydrolysates, to muconic acid using a model-guided strategy to maximize the theoretical yield. Using adaptive laboratory evolution (ALE) and metabolic engineering in a strain engineered to express the D-xylose isomerase pathway, we demonstrate that mutations in the heterologous D-xylose:H + symporter (XylE), increased expression of a major facilitator superfamily transporter (PP_2569), and overexpression of aroB encoding the native 3-dehydroquinate synthase, enable efficient muconic acid production from glucose and xylose simultaneously. Using the rationally engineered strain, we produce 33.7 g L −1 muconate at 0.18 g L −1 h −1 and a 46% molar yield (92% of the maximum theoretical yield). This engineering strategy is promising for the production of other shikimate pathway-derived compounds from lignocellulosic sugars. Muconic acid is a platform chemical with wide industrial applicability. Here, the authors report efficient muconate production from glucose and xylose by engineered Pseudomonas putida strain using adaptive laboratory evolution, metabolic modeling, and rational strain engineering strategies.